Predicting Future Shifts in the Distribution of Tropicalization Indicator Fish that Affect Coastal Ecosystem Services of Japan - Sudo, Kenji; Maehara, Serina; Nakaoka, Masahiro; Fujii, Masahiko (Frontiers in Built Environment, 2022)
Tropicalization characterized by an increase in marine species originating from the tropical waters affects human society in various ways. An increase in toxic harmful species negatively affects fisheries and leisure use, and an increase in herbivorous fish affects fisheries and carbon sink capacity by decreasing seagrass/seaweed beds. On the other hand, an increase in tropical reef fish attract more tourism. This study aimed to predict future shifts in the distribution of functional groups of tropicalization indicator fish that can affect marine ecosystem services in temperate coastal waters of Japan. We estimated the distribution of harmful fish Aluterus scriptus and Scarus ovifrons, herbivorous fish Kyphosus bigibbus and Siganus fuscescens, and tropical reef fish Amphiprion frenatus and Chaetodon auriga by collecting their distribution data from open databases. Distributions in 2000–2018 and the future (2046–2055 and 2091–2100) under different climate change scenarios (the representative concentration pathways; RCPs) were estimated using a species distribution model. We used environmental variables such as sea surface temperature (SST), depth, slope, coral reef area, and seagrass/seaweed bed area as predictors, and carried out future predictions using future ocean regional projection (FORP) datasets. The minimum SST was the factor most responsible for the estimated distribution patterns for all species. The depth, slope and seagrass/seaweed bed were also important for some species. The estimated probability of occurrence was high along the Pacific coast, which was affected by the Kuroshio warm current and Tsushima current along the coast of the Sea of Japan. Projected shifts in distributions based on different RCP scenarios showed that these indicator species would significantly increase their distribution in the middle to northern parts. By the 2090s, their habitat range was estimated to increase to 1.2–1.9 times that of 2000–2018 with severe warming (RCP8.5). However, the target species habitat range would not change significantly with stringent mitigation (RCP2.6). Our results suggest that ambitious commitment to reducing CO2 and other greenhouse gas emissions, such as following the Paris Agreement, will alleviate future tropicalization. Moreover, the fine resolution results can also be directly used for planning climate adaptation programs for local decision makers.